Hubungan Indeks Kepuasan Pasien tentang Mutu Pelayanan Dimensi Jaminan dengan Minat Berobat Kembali di Poli Interna RSD Kalisat Jember (The Relationship between Patient’s Satisfaction Index on Assurance of Service Quality and Utility at Internal Medicine - Zuliyatul Masnunah; Dwita Aryadina Rachmawati; Sugiyanta Sugiyanta (Pustaka Kesehatan, 2017)
The increasing number of hospitals causes competition among hospitals to get patients so that each hospital must provide quality services to reach patient’s satisfaction. Patient’s satisfaction determines patients behavior in the future, include their interest in utility. The purpose of this study was to find out the relationship between patient satisfaction index on assurance of service quality and utility. This study used cross-sectional design with 50 respondents. Patient’s satisfaction index and utility were measured using ServQual questionnaire. The results of statistic test with Spearman's Rho correlation test showed that the significance (p) = 0,030 with correlation coefficients (r) = 0.308. So, it can be concluded that there was a weak relationship between patient’s satisfaction index about assurance of service quality and utility at Interna Medicine Polyclinic Kalisat Hospital Jember. Keywords: Patient’s satisfaction, service quality, assurance, utility.